2009
DOI: 10.1016/j.ejcts.2008.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Combined videothoracoscopic and videomediastinoscopic approach improves radicality of minimally invasive mediastinal lymphadenectomy for early stage lung carcinoma☆

Abstract: A combined approach by VATS and VAMLA improves radicality of minimally invasive mediastinal lymphadenectomy without increase in operation time, morbidity, and drainage time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 15 publications
(19 reference statements)
2
23
0
Order By: Relevance
“…The role of transcervical lymphadenectomies in early stage lung cancer has been described, showing better staging values than standard mediastinoscopy and endoscopic ultrasound fine needle aspiration techniques (14)(15)(16)(17)(18). Therefore, in case of central tumours, the accuracy of these techniques adds value to rule out mediastinal disease, enhancing, therefore, clinical staging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of transcervical lymphadenectomies in early stage lung cancer has been described, showing better staging values than standard mediastinoscopy and endoscopic ultrasound fine needle aspiration techniques (14)(15)(16)(17)(18). Therefore, in case of central tumours, the accuracy of these techniques adds value to rule out mediastinal disease, enhancing, therefore, clinical staging.…”
Section: Discussionmentioning
confidence: 99%
“…Other challenging situations like bilateral synchronous lung cancer (16,19) and elderly patients or patients with poor performance status (16) can benefit from VAMLA/TEMLA in order to avoid unnecessary lung resections and its complications. Finally, these pre-resectional lymphadenectomies can be indicated in cIA tumours located in the left lung or in combination with VATS lobectomy to achieve a radical lymphadenectomy, even better than by open surgery (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an exception, Witte et al (11) evaluated the feasibility and radicality of a combined thoracoscopic and mediastinoscopic approach to improve minimally invasive mediastinal LN dissection: they compared the number of dissected stations and sample weight in a group of 14 patients who underwent VATS lobectomy alone versus a group of 18 patients who underwent a combined VAMLA and VATS lobectomy. They concluded that VAMLA improves radicality of minimally invasive mediastinal lymphadenectomy without increasing operation time, morbidity, and drainage time.…”
Section: Discussionmentioning
confidence: 99%
“…A combined mediastinoscopic approach [video-assisted mediastinoscopic lymphadenectomy (VAMLA)] has been advocated to achieve a more satisfying radical minimally invasive lymphadenectomy during VATS lobectomy (11). However, VAMLA is not universally performed and it is a safe procedure only in experienced hands.…”
Section: Introductionmentioning
confidence: 99%